Pressure-dependence of mechanical properties and thermodynamic behavior of hexagonal and orthorhombic Ti3Sn: A first-principles investigation. (January 2023) - Yang, Jianbing; Zhao, Yanjun; Pang, Mingjun; Zhao, Lingfeng; Xie, Cong; Wei, Fenggui; Pang, Xingzhi
Abstract: The influence of pressure on the mechanical, thermodynamic and electronic properties of orthorhombic and hexagonal Ti3 Sn compounds was investigated by using first-principles calculations. The pressure–lattice parameters relationships of both compounds can be obtained by applying hydrostatic pressure. According to the curves of elastic constants as a function of pressure, it is revealed that high pressure improves the resistance to elastic moduli of orthorhombic Ti3 Sn compound as well as bulk modulus of hexagonal phase. Both compounds are considered as ductile materials in the range of 0–100 GPa. It is demonstrated that the high pressure can effectively enhance the Debye temperature and minimum thermal conductivity of orthorhombic Ti3 Sn compound, whereas hexagonal phase has the maximum values at 10 GPa. Results of electronic structures indicate that the p-d hybridization between Sn and Ti atoms of orthorhombic Ti3 Sn compound is stronger than that of hexagonal phase. Highlights: High pressure in the range of 0–100 GPa improves the elastic moduli of orthorhombic Ti3 Sn compound. The orthorhombic and hexagonal Ti3 Sn compounds exhibit ductile behavior in the range of 0–100 GPa. The Debye temperature and minimum thermal conductivity of both compounds as a function of pressure can be predicted.